1999
DOI: 10.1164/ajrccm.160.5.9808139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hallway and Treadmill Six-minute Walk Tests

Abstract: The 6-min walk test (SMWT) performed in the hallway (HW) is used as a clinical indicator of functional capacity in patients with lung disease. A 6-min walk test utilizing a treadmill (TM) is easier to perform and allows easier patient monitoring. Therefore, we formulated a standardized TM SMWT protocol and compared the results with those of a HW SMWT. All patients were enrolled in a pulmonary rehabilitation program. Patients with current infection, recent change in inhaled medications or oral steroid use, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
8
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 12 publications
8
105
8
7
Order By: Relevance
“…Standard error of measurement as a percentage of the mean was 5%, which was similar to the same error analysis using the 6-min walk test in other studies that also represented ϳ5% of the mean performance of the test. 21,25 These results show that the performance in this test was not influenced by the learning effect in the COPD population, which leads to the affirmation that this test can be done without a familiarization test, spending only 15 min of assessment time. This characteristic could be an advantage over the 6-min walk test, which requires at least one previous test and a recovery time between them, totaling a time expenditure of at least 50 min.…”
Section: Discussionsupporting
confidence: 54%
“…Standard error of measurement as a percentage of the mean was 5%, which was similar to the same error analysis using the 6-min walk test in other studies that also represented ϳ5% of the mean performance of the test. 21,25 These results show that the performance in this test was not influenced by the learning effect in the COPD population, which leads to the affirmation that this test can be done without a familiarization test, spending only 15 min of assessment time. This characteristic could be an advantage over the 6-min walk test, which requires at least one previous test and a recovery time between them, totaling a time expenditure of at least 50 min.…”
Section: Discussionsupporting
confidence: 54%
“…In some studies, the achieved distances were comparable, 25 while in other areas the treadmill distance was nearly 15% lower. 26 This may reflect the need for constant pace changing and possibly problems of balance for people not familiar with treadmill walking.…”
Section: Treadmill 6-minute Walkmentioning
confidence: 86%
“…A previous study, also involving COPD patients walking on a treadmill, (6) provided evidence of the need to perform the tread6MWT at least twice in order to obtain a reproducible value. Similar findings have been reported regarding the hallway 6MWT, which is why it is necessary to conduct a first test in patients who have never performed the test before, i.e., to increase the reproducibility of the test.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between the original (hallway) 6MWT and the tread6MWT in COPD patients has demonstrated that, although the tread6MWT is not comparable to the 6MWT in terms of the distance covered, it is a satisfactory alternative for the functional evaluation of COPD patients. (6) However, various factors should be considered before conducting the tread6MWT, e.g., whether or not to develop an incremental speed and inclination protocol and whether the speed should be controlled by the patient or the technician responsible for the examination.…”
Section: Introductionmentioning
confidence: 99%